2019
DOI: 10.22456/1679-9216.93775
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Profile and Productive Performance in Dairy Cows with Lameness During Postpartum Period

Abstract: Background: Lameness in dairy cows is classified as a gait change caused by multifactorial process. The phase of the peripartum causes intense physiological changes for the adaptation of late gestation and onset of lactation. The aim of this study was to characterize the changes in the biochemical profile and productive performance in dairy cows with lameness during postpartum period. A total, of 48 multiparous (2 to 3 lactations and 3-4 years old) dairy cows, that had the milk production of 9,200 kg/ dairy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
4
11
0
1
Order By: Relevance
“…Regarding cholesterol concentration, our data are in agreement with Kaneene, Miler, Herdt, and Gardiner (1997), who observed a lower concentration of cholesterol during the postpartum period in cows with metritis when compared to cows without metritis. Cholesterol is considered acute‐phase reactants of inflammation, which can contribute to the diagnosis of intense pro‐inflammatory status (Paiano, Birgel, Ollhoff, & Birgel Junior, 2019). Kim and Suh, (2003) showed that dairy cows with lower concentration of cholesterol were more likely to developed uterine diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cholesterol concentration, our data are in agreement with Kaneene, Miler, Herdt, and Gardiner (1997), who observed a lower concentration of cholesterol during the postpartum period in cows with metritis when compared to cows without metritis. Cholesterol is considered acute‐phase reactants of inflammation, which can contribute to the diagnosis of intense pro‐inflammatory status (Paiano, Birgel, Ollhoff, & Birgel Junior, 2019). Kim and Suh, (2003) showed that dairy cows with lower concentration of cholesterol were more likely to developed uterine diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Low total cholesterol concentration was observed for all groups with metabolic diseases. Cholesterol is a component of lipoproteins, forming lipid composition of cell membranes, its measurement helps assess liver functionality, and cholesterol is considered a negative acute‐phase reactant (Paiano et al, 2019c). The monitoring of serum cholesterol (for cows with hypocalcemia on days 21 and 2 prepartum, hyperketonemia at 21 days before calving and at parturition, and lipomobilization at 21 days before parturition) can contribute to the identification of dairy cows at risk of developing metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…So, to accommodate the increased energy demand with decreased blood glucose levels, internal reserves are mobilised to provide NEFA partly as a direct fuel or partially oxidized by liver into ketone body, mainly BHB (reviewed by Abdelli et al., 2017; McArt et al., 2013; Ospina et al., 2013; Wathes et al., 2013). Nutritional metabolites such as NEFA, BHB, and glucose are involved in postpartum energy homeostasis and restoration of ovarian activity in cattle (Konigsson et al., 2008; Obese et al., 2015; Paiano et al., 2019; Paiano, Lahr, et al., 2019). Decreased concentrations of glucose and elevated levels of NEFA in blood due to mobilization of body reserves to support milk production have been associated with delayed resumption of ovarian activity in cattle, presumably due to suppression of the frequency luteinizing hormone (low LH pulse frequency) and subsequent reduced concentrations of oestradiol, which is ineffective to induce LH surge and ovulation (Roche et al, 2006; Giuliodori et al., 2011; Wathes et al., 2013).…”
Section: Introductionmentioning
confidence: 99%